2013
DOI: 10.1088/0004-637x/773/1/71
|View full text |Cite
|
Sign up to set email alerts
|

A MOLECULAR LINE SURVEY OF THE CARBON-RICH PROTOPLANETARY NEBULA AFGL 2688 IN THE 3 mm AND 1.3 mm WINDOWS

Abstract: We present a spectral line survey of the proto-planetary nebula AFGL 2688 in the frequency ranges of 71-111 GHz, 157-160 GHz, and 218-267 GHz using the Arizona Radio Observatory 12 m telescope and the Heinrich Hertz Submillimeter Telescope. A total of 143 individual spectral features associated with 32 different molecular species and isotopologues were identified. The molecules C 3 H, CH 3 CN, H 2 CO, H 2 CS, and HCO + were detected for the first time in this object. By comparing the integrated line strengths … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 54 publications
3
19
2
Order By: Relevance
“…for the protoplanetary Calabash Nebula, while in CRL 2688, Zhang et al (2013) found f(HNC/H 2 )∼5.7×10…”
Section: Hnc Abundance and Distribution In Planetary Nebulaementioning
confidence: 95%
“…for the protoplanetary Calabash Nebula, while in CRL 2688, Zhang et al (2013) found f(HNC/H 2 )∼5.7×10…”
Section: Hnc Abundance and Distribution In Planetary Nebulaementioning
confidence: 95%
“…Some examples are the C-rich AGB star IRC+10216 [41,42], probably the best studied AGB star, and the O-rich AGB stars IK Tau and R Dor [43,44]. The chemistries of a number of pPNe are also relatively well characterized, particularly the C-rich pPNe CRL 618 [45] and CRL 2688 [46] and the O-rich source OH 231.8+4.2 [47,48].…”
Section: Circumstellar Chemistrymentioning
confidence: 99%
“…Presented in Figure 6 are the rotational diagrams of the cyanopolyyne molecules detected in CRL 2688. Since the present survey only covers the low energy range and the thermal structure within the CSE is often stratified, data points from previous high-frequency surveys (Zhang et al 2013;Chau et al 2012) have been concatenated with those from the present study for a more reliable estimate of the excitation temperatures and column densities. Results from rotational analysis of cyanopolyyne emission from CRL 2688 and IRC+10216 are presented in Table 4.…”
Section: Cyanopolyynesmentioning
confidence: 99%
“…In particular, the survey of Gong et al (2015), which covered the 17.8 -26.3 GHz frequency range, detected a total of 78 transitions from known molecular species, amongst which 23 were detected for the first time outside the solar system. Our research group has been engaged in a long-term project to perform systematic spectral line surveys in a large sample of evolved stars with comprehensive wavelength coverage (He et al 2008;Zhang et al 2008Zhang et al , 2009aChau et al 2012;Zhang et al 2013). In the present paper, we investigate the 20-25 GHz spectra of a sample consisting of C-rich CSEs including IRC+10216, CRL 2688, CRL 618, and NGC 7027. Displayed in Table 1 are the physical properties of the scientific objects consolidated from a series of literature searches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation